SIKAP INDONESIA NATIONAL AIR CARRIERS ASSOCIATION(INACA)DALAM KEBIJAKAN LIBERALISASI LAYANAN UDARA ASEAN OPEN SKY 2015 - ", Roby; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research focused on Inaca (Indonesian National Air Carriers Assosiation)'s act towards ASEAN open sky 2015's policy. The commercial flight industries had shown some bussinesses with the cooperation of many countries in air transport services. The purpose was to anticipate the changes of that flight industries. This cooperation took places in many region of the world such as North America, South America, Europe, Pacific and Southeast Asia. In fact, there differences on the aspects of this open sky cooperation. This strategy can be done in bilateral, regional, or multilateral levels.In particular, open sky drove flight companies to a tight competition, and brought the possibility for the "third nation" to participate in serving routes between the two countries, and gave the freedom for flight companies to expand their routes and links in accordance with the active laws. However, Inaca assumed that this policy only gave benefit to the small geographical countries with limited airport, and Indonesia will only become a market to the ASEAN countries.Keywords : ASEAN open sky policy, National Interest, Inaca, ASEAN open sky.